Systematic Analyses of the Role of the Reader Protein of N6-Methyladenosine RNA Methylation, YTH Domain Family 2, in Liver Hepatocellular Carcinoma - Shao, Xiang-yang; Dong, Jin; Zhang, Han; Wu, Ying-song; Zheng, Lei (Frontiers in Molecular Biosciences, 2020)
Background: YTH domain family 2 (YTHDF2) acts as a reading protein for RNA methylation, which is important in tumors regulation by RNA methylation. However, the effect of YTHDF2 in Liver hepatocellular carcinoma (LIHC)which still requires elucidated. Methods: We explored the role of YTHDF2 in LIHC based on publicly available datasets (TCGA, ICGC, GEO). Bioinformatics was performed to analyze the YTHDF2 gene: Logistic regression analysis was applied to analyze the correlation between YTHDF2 expression and clinical characteristics. To evaluate the effect of YTHDF2 on the prognosis of LIHC patients was analyzed using Kaplan-Meier (KM) plotter. Gene set enrichment analysis (GSEA) was performed using the TCGA dataset. Univariate and Multivariate Cox analysis were used to analyze that the correlations between YTHDF2 expression and Clinic pathologic characteristics with survival. Co-expression genes with YTHDF2 were identified and detected using publicly available datasets (LinkedOmics, UCSC, GEPIA, and GEO). In addition, the correlations between YTHDF2 and immune infiltrates were investigated by TIMER and GEPIA. Results: Here, we found that the mRNA and protein levels of YTHDF2 were significantly higher in LIHC tissues than in non-cancerous tissues, and high YTHDF2 expression in LIHC was associated with poor prognostic clinical factors (high stage, grade, T classification). KM analysis indicated that high YTHDF2 level was correlated with unfavorable prognosis. Moreover, Univariate and Multivariate Cox analysis revealed that YTHDF2 was an independent factor for poor prognosis of LIHC patients. GSEA revealed that YTHDF2 high expression phenotype are consistent with the molecular pathways implicated in LIHC carcinogenesis. ROC curve analysis shows that YTHDF2 might have diagnostic value in LIHC patients. Co-expression analysis determined that YTHDF2 was positively associated with SF3A3, implying they may cooperate in liver cancer progression. Besides, YTHDF2 expression is associated with immune infiltration levels and immune marker sets. YTHDF2 has the potential to regulate tumor-associated macrophages (TAM) polarization, induce T cell exhaustion, and activate Tregs cells. Conclusion: YTHDF2 may be a promising biomarker for the diagnosis and prognosis and may provide new directions and strategies for the treatment of LICH patients.